PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR IPA PADA PEMBELAJARAN TEMATIK MENGGUNAKAN PBL - Erviyanti Pramudya; Firosalia Kristin; Indri Anugraheni (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2019)
The purpose of this research is to explain the steps of Problem Based Learning model to increase student involvement in learning and the result of the learning, knowing the enhancement of the student involved, and knowing the growth of student’s learning result. The form of this research is Classroom Action Research which it should be done in two cycles. This research has been done in First Noborejo National Elementary School and the subject of this research is fourth-grade students consists of 34 people. The data collection technic of this research is using test and non-test technic. The technic that we used to analyze all the data is quantitative and qualitative descriptive analysis. The result of this research showing that applying steps of Problem Based Learning Model which is orientated student on the problem, organizing student to learn, guide the individual and social experience, developing and providing masterpiece of the student, also analyzing and evaluating problem-solving process, an increased student involved and science learning outcomes in thematic learning on fourth grade student of First Noborejo National Elementary School. The proof of this research’s result is the growth of students involved from their first condition (pre-cycle) which was 77,47 and categorized as less active and after using this model, for the first cycle, it increased and reached 95,44 with category pretty active. In the second cycle, the average of the student involved increased become 118,32 with category active. The student learning outcomes also increased with the first learning outcomes average (pre-cycle) is 62,17 and only 13 students that pass the test (38,23%). It becomes better with the average grades of student’s learning outcomes is 78,39 and 23 students passed the test (67,64%). On the second cycle, the average grades of the student learning outcomes are 83,29 and 28 students passed the test (82,36).